دور الاستراتيجيات الحديثة لإدارة الأزمات في تحسين الأداء التسويقي (دراسة ميدانية على المصارف الخاصة في محافظة اللاذقية) - صالح, كاترين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يعد التعامل مع الأزمات أحد أهم محاور اهتمام الإدارة في ظل التحديات المستمرة التي تواجهها المنظمات، ويتطلب ذلك وجود إدارة على درجة عالية من الكفاءة والقدرة على التفكير الإبداعي من أجل اتخاذ الخطوات المناسبة والمدروسة بالسرعة الممكنة، وذلك بهدف تجاوز الأزمة وضمان الاستمرار والبقاء واستثمار الفرص الناتجة عنها بما يحسن الأداء العام للمنظمة، وتعد الاستراتيجيات الحديثة لإدارة الأزمات من أكثر الاستراتيجيات فعالية في إدارة الأزمات وتحسين الأداء. يهدف البحث إلى تقييم الاستراتيجيات الحديثة لإدارة الأزمة الراهنة في المصارف الخاصة العاملة في محافظة اللاذقية، ودورها في تحسين الأداء التسويقي للمصارف المدروسة، ودراسة طبيعة وقوّة العلاقة بينهما. ولتحقيق ذلك تمّ صياغة أربع فرضيّات، واعتمدت الدّراسة المقاربة الاستنباطيّة؛ وتمّ استخدام المنهج الوصفي التّحليلي لتوصيف متغيّرات الدراسة، واستخدمت الباحثة أسلوب الاستبانة لجمع البيانات الّتي تمّ تحليلها باستخدام اختبارات إحصائيّة أهمّها: اختبار الوسط الحسابي One- Sample T. test، واختبار الارتباط الثّنائي Pearson Correlation، واختبار الانحدار المتعدد. وقد توصلت الباحثة إلى عدّة نتائج أهمّها: توجد علاقة طردية بين الاستراتيجيات الحديثة لإدارة الأزمة وبين الأداء التسويقي، كما يوجد تأثير ذو دلالة إحصائية لكل من استراتيجية تغيير المسار واستراتيجية فرق العمل على الأداء التسويقي، ولا يوجد تأثير ذو دلالة إحصائية لاستراتيجية تفتيت الأزمة على الأداء التسويقي في المصارف المدروسة. Crisis management is one of the most important areas of management's concern in light of the ongoing challenges faced by organizations. This requires a highly competent management and creative thinking to take the appropriate steps as quickly as possible, in order to overcome the crisis and ensure continuity, improving the overall performance of the Organization. Modern crisis management strategies are the most effective strategies for crisis management and performance improvement. The research aims at evaluating the modern strategies for managing the current crisis in the Syrian private banks in the province of Lattakia and its role in improving the marketing performance of the studied banks, and studying the nature and strength of the relationship between them. To achieve this, four hypotheses were formulated, and the study adopted the descriptive approach; the descriptive analytical method was used to describe the variables of the study. The researcher used the questionnaire method to collect the data analyzed using statistical tests, the most important of which were: the one-sample T. test, the Pearson Correlation, and the multiple regression test. The researcher reached several results, the most important of which are: There is a positive relationship between the modern crisis management strategies and the marketing performance. There is also a statistically significant effect for both of the changing path strategy and the teams work strategy on marketing performance. There is no statistically significant effect of the crisis fragmentation strategy on marketing performance Banks studied.